Ruptured Left Gastric Artery Aneurysm Associated with Fibromuscular Dysplasia. (February 2022) - Ho, Kelvin K. F.; Foo, Gary; Bingley, John; Redmond, Kendal
Background: Fibromuscular dysplasia is a non-inflammatory, non-atherosclerotic vascular disease that commonly affects renal and carotid arteries but involvement of virtually any vascular territory has been observed. Research Design/ Study sample: This is a case report of a ruptured left gastric artery aneurysm as the first presentation of fibromuscular dysplasia. Data collection: After written consent from the patient, relevant clinical notes and imaging were retrospectively reviewed and critically analysed. Purpose: This case reiterates the importance of considering fibromuscular dysplasia as an uncommon cause of visceral artery aneurysms. In addition, this case shows that the impact of visceral artery vasospasm on endovascular access should not be underestimated and subsequent attempts can be successful after a period of resuscitation. Results: After initial difficulty in endovascular treatment due to visceral vasospasm, the case was successfully managed with with staged open ligation and endovascular embolization after a period of resuscitation. Conclusions: FMD is an important differential diagnosis to consider in cases of visceral aneurysms.